JOB SATISFACTION OF PRIMARY SCHOOL TEACHERS IN RELATION TO THEIR SELF ESTEEM - Beri, Dr. Nimisha; Arora, Supriya (IJRDO - Journal of Social Science and Humanities Research, 2016)
The present study was aimed to find the Job Satisfaction of primary school teachers in relation to their self esteem. A study was conducted on 150 teachers (75 males and 75 females) selected randomly from government and private schools of Jalandhar district. Descriptive survey method was used to collect the data. The tools used for data collection were Job satisfaction scale by Dr Amar Singh & Dr T .R. Sharma and Self Esteem Scale by Morris Rosenberg. After the analysis of the data it was found that female teachers with high self esteem are more satisfied than female teachers with low self esteem. It is clear from the findings of the study that male primary school teachers with high self esteem have more job satisfaction than male teachers with low self esteem. The results of the study showed that there is significant positive relationship between Self esteem and Job satisfaction.